Whole-body in-vivo neutron activation analysis in assessing treatment of renal osteodystrophy with 1-alpha-hydroxycholecalciferol. Issue 6027 (10th July 1976) - Naik, R B; Gosling, P; Price, C P; Robinson, B H; Dabek, J T; Heath, D A; James, H M; Kanis, J A; Smith, R
Abstract : Four selected adults with different patterns of osteodystrophy receiving regular dialysis were treated with 1-alpha-hydroxycholecalciferol (1-alpha-OHD3) 0-5-2 mug/day for 10 to 12 months. In two patients, one with osteitis fibrosa and the other with osteomalacia, significant biochemical, radiological, and histological improvements occurred, and total body calcium measured by in-vivo neutron activation analysis increased. In two patients, in whom there were no increases of whole-body calcium, neither biochemical improvement nor healing of bone lesions occurred during the study; in one of these patients the effect of 1-alpha-OHD3 on bone resorption may have contributed to loss of body calcium and deterioration of bone disease. 1-alpha-OHD3 may therefore be a valuable adjunct in the treatment of only some patients with renal osteodystrophy. Whole-body in-vivo neutron activation seems to provide a sensitive and non-invasive index of early response to treatment.